The Intra-Industry Transfer of Information Inferred From Announcements of Corporate Security Offerings. - Szewczyk, Samuel H (Journal of Finance, 1992)
This study investigates the extent to which information inferred by investors from initial announcements of corporate security offerings affects share prices in the capital markets. The empirical tests measure the response in the common stock prices of both firms announcing a security offering and nonannouncing firms operating in the same industry. Small but significantly negative abnormal returns are shown by industry shares upon initial announcements of common stock, convertible debt, and straight public offerings. Such an industry response indicates that share prices incorporate an inside assessment of factors relevant to the valuation of an industry subset of firms.